Thermal Stability of Sputtered Tungsten Nitrides for Solar Thermal Applications - Anna Castaldo; Emilia Gambale; Laura Iemmo (Applied Sciences, 2022)
In this work, tungsten nitrides sputtered at different powers supplied to a W target (300 W, 500 W, 700 W) and proposed for solar thermal applications as part of solar absorbers, as active and robust materials for capacity energy storage and as plasma-facing materials were annealed in vacuum at medium-high temperatures (470 °C, 580 °C) and characterized by means of X-ray diffraction (XRD), AFM, micro-Raman, FTIR, UV–VIS–-NIR, sheet, surficial energy and wetting angle measurements. From the overall set of analyses, some important modifications and differences between samples after annealing emerged (which will be useful for selecting them for specific applications) and have been correlated to sputtered W metallic clusters’ ability to adsorb, form complexes with and react with the strong N2 triple bond under the various plasma conditions of a reactive sputtering process. In particular, the 300 W film of poor crystalline quality as deposited, after annealing released entrapped nitrogen and retained its W2N structure up to a temperature of 580 °C. Despite there being no phase transition, there was an increase in sheet resistance, which is detrimental because the preservation of metallic character is an important requisite for the proposed applications. The 500 W film had a stable crystalline structure and a metallic character unmodified by increasing temperature. The 700 W film, whose structure as deposited was almost amorphous, underwent the most severe modification after annealing: crystallizing, disproportioning and giving rise to a composite and porous nature (W + WNx) not ideal for spectrally selective coating applications, but useful for tailoring capacitive energy storage devices, or for catalysts for hydrogen evolution reactions (as an alternative to platinum) in alkaline water electrolysis.